1991
DOI: 10.1101/gad.5.1.74
|View full text |Cite
|
Sign up to set email alerts
|

DNA-protein interaction at the replication termini of plasmid R6K.

Abstract: Understanding the molecular mechanism of specific and polarized termination of DNA replication at a sequence-specific replication terminus requires detailed analyses of the interaction of terminator protein {ter) with specific DNA sequences (T], constituting the replication terminus. Such analyses should provide the structural basis of the functional polarity of replication inhibition observed in vivo and in vitro at T sites. With this objective in mind, we have purified the replication terminator protein of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 32 publications
1
34
1
Order By: Relevance
“…Although both our in vitro results reported here and our in vivo data (32) showed that a C6 to A6 in transversion in Ter did not manifest any loss of arrest of a sliding or unwinding DnaB, another group (33) has reported that the same mutation can cause a 3-fold reduction in fork arrest. This incremental reduction in fork arrest perhaps can be reconciled with other observations as discussed below.…”
Section: Discussioncontrasting
confidence: 68%
“…Although both our in vitro results reported here and our in vivo data (32) showed that a C6 to A6 in transversion in Ter did not manifest any loss of arrest of a sliding or unwinding DnaB, another group (33) has reported that the same mutation can cause a 3-fold reduction in fork arrest. This incremental reduction in fork arrest perhaps can be reconciled with other observations as discussed below.…”
Section: Discussioncontrasting
confidence: 68%
“…9) is now predicted for a complex that is in equilibrium between a specifically bound form and a nonspecifically bound form. Furthermore, this suggests that such sites could spread farther in cases where the specific binding is weaker, such as with TerR2, as is observed (54,158). This can also explain an apparent discrepancy between results on the effects of the R198A mutation.…”
Section: Prospects For the Futurementioning
confidence: 79%
“…3), both groups reported protected sites outside this region. Sista et al (158) found four such sites, between 1 and 3 base pairs preceding and 1 following the Tus-binding site in the TerR2 sequence (Fig. 9).…”
Section: Dna Modification and Protection Studiesmentioning
confidence: 94%
See 2 more Smart Citations